Methodology of fibroblast and mesenchymal stem cell coating of surgical meshes: A pilot analysis. Issue 4 (21st October 2013) - Gao, Yue; Liu, Li‐Jia; Blatnik, Jeffrey A.; Krpata, David M.; Anderson, James M.; Criss, Corry N.; Posielski, Natasza; Novitsky, Yuri W.
Abstract Coating of various synthetic, absorbable, and biologic meshes with mesenchymal stem cells (MSCs) and fibroblasts was analyzed qualitatively and quantitatively. Five hernia meshes—light weight monofilament polypropylene (Soft Mesh), polyester (Parietex‐TET), polylactide composite (TIGR), heavy weight monofilament polypropylene (Marlex), and porcine dermal collagen (Strattice)—were coated with three cell lines: human dermal fibroblasts (HFs), rat kidney fibroblasts (NRKs), and rat MSCs. Cell densities were determined at different time points. Samples also underwent histology and transmission electron microscopic (TEM) analyses. It required HFs 3 weeks to cover the entire mesh, while only 2 weeks for NRKs and MSCs to do so. MSCs had no preference for any of the meshes and produced the highest cell densities on Parietex and TIGR. Substrate‐preference accounted for the significantly lower fibroblast densities on TIGR than Parietex. Fibroblasts failed to coat Marlex. Strattice, which had the least surface area, generated comparable cell densities to Parietex. Both histology and TEM confirmed cell coating of mesh surface. Various prosthetics can be coated by certain cell strains. Both mesh composition and cell preference dramatically influence the coating process. This methodology provides foundation for novel avenues of modulation of host response to various modern synthetic and biologic meshes. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 797–805, 2014.